Characteristics and treatment strategies of aggressive angiomyxoma in women: A retrospective review of 87 cases - Wang, Yang; Bu, Xiaoling; Liu, Yanxia; Xing, Yu; Tong, Qing (Frontiers in Surgery, 2023)
Objective Aggressive angiomyxoma (AAM) is a rare kind of soft tissue tumor. The purpose of this study is to summarize the clinical manifestations and treatment strategy of AAM in women. Method We searched the case reports on AAM in EMBASE, Web of Science and PubMed, China biomedical database, Wanfang database, VIP database, and China National Knowledge Internet from the start of database construction to November 2022 without any language restrictions in place. Then, the obtained case data were extracted, summarized, and analyzed. Result A total of 74 articles were retrieved involving 87 cases. The age ranges of onset were 2–67 years. The median age at onset was 34 years. The size of the tumor varied greatly among individuals, and about 65.5% of them were asymptomatic. MRI, ultrasound, and needle biopsy were used for diagnosis. Surgery was the primary mode of treatment, but it was prone to relapse. Gonadotropin-releasing hormone agonist (GnRH-a) might be used to reduce the tumor size before the operation and prevent recurrence after the operation. For patients who are unwilling to receive surgical treatment, GnRH-a alone could be attempted. Conclusion Doctors should consider the possibility of AAM in women with genital tumors. For surgery, it must be ensured that the negative surgical margin is recommended and achieved for preventing recurrence, but we should not ignore the impact of the excessive pursuit for a negative margin on the patient’s reproductive function protection and postoperative recovery. Long-term follow-up is necessary regardless of whether patients receive medical treatment or surgical treatment.